The Influence of Brain-Based Learning Model with Cultural Context on Critical Thinking Skills and Self-Efficacy - Izwita Dewi; Ade Andriani; Hasratuddin Siregar; Robby Rahmatullah (Didaktik Matematika, 2024)
This study examines the interplay between critical thinking and self-efficacy, two skills that reinforce each other in learning. Critical thinking enhances students' confidence, while self-efficacy drives the continuous development of critical thinking across contexts. The research aims to (1) evaluate the effect of a brain-based learning model integrating cultural context on students' critical thinking and self-efficacy and (2) assess the model's effectiveness in enhancing these skills. Using a quasi-experimental design, the study involved Year 7 students selected through purposive sampling and divided into experimental and control groups. The experimental group was taught using the brain-based learning model with cultural context, while the control group received conventional instruction. Data were collected through pretests, posttests, and self-efficacy questionnaires. Findings revealed that the brain-based learning model with cultural context significantly improved critical thinking and self-efficacy, with the experimental group outperforming the control. Furthermore, the experimental group showed a marked increase in both skills following the intervention. The study concludes that integrating brain-based learning and cultural context, particularly in mathematics, effectively fosters critical thinking and self-efficacy and recommends its adoption in teaching practices.